Re-engineering closing watersheds: the negotiated expansion of a dam-based irrigation system in Bolivia - López, R.R.; Vincent, L.; Rap, Edwin (Informa UK Limited, 2015)
The expansion of the Totora Khocha dam-based irrigation system in the Pucara watershed is a case of planned re-engineering of a closing watershed. This article shows how, when irrigation systems expand in space and across boundaries to capture new water, they also involve new claims by existing and emergent users. This results in complex processes of design, contestation and negotiated redesign, where irrigation projects are being produced by the negotiated construction of water networks. Therefore, the design process in a closing watershed is better approached as a dynamic and negotiated process of engineering than as a prescriptive mode of network building.